The Development of Inquiry-Based Teaching Materials to Improve Physics Teacher's Conseptual Understanding - Lovy Herayanti; Habibi Habibi; Baiq Azmi Sukroyanti (Jurnal Penelitian Pendidikan IPA, 2022)
This development research aims to produce a product in the form of a valid and effective inquiry-based learning tool to increase the conceptual understanding of prospective physics teachers. The products that were developed include SAP (Satuan Acara Perkuliahan) or lecture unit, and LKM (Lembar Kerja Mahasiswa) or worksheet, Teaching Materials and conceptual understanding test instruments. The research design used is a 4D model consisting of Define, Design, Develop and Disseminate. Data collection techniques used validation sheets and evaluation tests for conceptual understanding. The validity data was analyzed using a Likert scale. Product effectiveness data was analyzed using the Gain standard. Product validity was assessed by three expert validators. Assessment by the validator using criteria that are valid to strongly valid. The N-gain test for conceptual understanding showed values of 88.23% in the high category for the indicator of restating the concept and 62.81% in the medium category for the indicator of presenting the concept. The improvement in students' conceptual understanding as measured by the N-Gain test results after taking a pre-test and post-test can be used to determine the effectiveness of teaching materials developed by researchers. The pretest average score for the conceptual understanding instrument was 47.50 and for the posttest average score was 87.73. This value was then analyzed using the N-Gain test with a calculation result of 77.88%, which means that this value is classified into the high increase category. So, it can be concluded that the development of inquiry-based teaching materials to increase conceptual understanding of prospective physics teachers is valid and effective.